HUBUNGAN GAYA BELAJAR DENGAN KREATIVITAS SISWA MA DALAM MENYELESAIKAN SOAL CERITA MATEMATIKA - Fury Styo Siskawati (FKIP Universitas Islam Jember, 2016)
This research is aimed at investigating the correlation between learning style and creativity of MA student’s in solving the story-based mathematical problems. This is the corelational research with quantitative approach. The subjects of the research are the ten ggraders at MA Azza Ainul Yaqin. The subjects are given the test to know the creativity in solving the story-based mathematical problems. The data collection methods are documentation, questionnaire, and test. All the data gained in this study was analyzed by using Pearson Product Moment correlation coefficient. The result of the research are r product = 0.562 and r table = 0.413 it’s mean that r product > r table so accepted Ha and reject Ho. Thus, it can be concluded that there is a significant corelatiaon between learning style and creativity of MA student’s in solving the story-based mathematical problems. The suggestion is that the teacher must care about learning style and creativity student’s in order to make the student get maximum score in the school.Key Words: learnig style, creativity